KINERJA DINAS SOSIAL KOTA PEKANBARU DALAM PEMBERIAN BANTUAN SOSIAL SEMBAKO (STUDI KASUS DI KECAMATAN TENAYAN RAYA KOTA PEKANBARU) - Preselia Riski Mayliani; Abdul Sadad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The problem of poverty which is quite complex requires the intervention of all parties together and coordinated. Therefore, regional governments must budget funds for social assistance to people who are classified as poor to be assisted in their lives, especially during the Covid-19 pandemic, especially for Pekanbaru City in 2019 there are 324,000 people who are classified as poor and continue to increase, therefore the Government Pekanbaru City can provide social assistance to the affected poor vulnerable people in meeting their basic needs. One type of social assistance to the community is basic necessities, which is assistance given to almost all poor people. The Pekanbaru City Social Service has the role of coordinating social issues in the provision of Pekanbaru City social assistance, the role of the Pekanbaru City Social Service in distributing basic food assistance, starting from planning assistance needs, monitoring, coordinating and assisting in providing assistance. However, in the implementation of basic food social assistance to the community, there are still problems that can hinder these activities such as misappropriation of social assistance funds, the absence of socialization carried out by the government to the community. The purpose of this study was to determine and analyze the performance of the Pekanbaru City Social Service and the factors that influence the provision of basic food social assistance in Tenayan Raya District, Pekanbaru City. The research method used is qualitative. Data collection techniques were carried out by means of interviews, observation and documentation. The results of this study concluded that the performance of the Pekanbaru City Social Service in Providing Basic Food Social Assistance in Tenayan Raya District, Pekanbaru City according to the level of productivity achievement carried out by data collection and monitoring activities for the poor and the provision of basic food assistance has been going quite well. As for the influencing factors, among others, not all parties in the sub-district area who participated in the data collection of the basic food program, the number of human resources/implementers and the re-reporting were not given to the kelurahan party. Keywords: Performance, social assistance, basic necessities